2020
DOI: 10.1038/s41467-020-16616-8
|View full text |Cite
|
Sign up to set email alerts
|

p53 destabilizing protein skews asymmetric division and enhances NOTCH activation to direct self-renewal of TICs

Abstract: Tumor-initiating stem-like cells (TICs) are defective in maintaining asymmetric cell division and responsible for tumor recurrence. Cell-fate-determinant molecule NUMB-interacting protein (TBC1D15) is overexpressed and contributes to p53 degradation in TICs. Here we identify TBC1D15-mediated oncogenic mechanisms and tested the tumorigenic roles of TBC1D15 in vivo. We examined hepatocellular carcinoma (HCC) development in alcohol Western diet-fed hepatitis C virus NS5A Tg mice with hepatocyte-specific TBC1D15 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 35 publications
1
29
0
Order By: Relevance
“…Additionally, the NOTCH1 downstream effectors, HES1 and HEY1, promote integration of EMT and CSC self-renewal (31,32). Other work has shown that NOTCH1 interacts with NANOG in expanding CSCs (44). Along these lines, we found that the MUC1-CE2F1BAF pathway is necessary for expression of NOTCH1 and NANOG in PC cells.…”
Section: Muc1-c Regulates Lineage Plasticity In the Progression To Nepc By Activating In Part Asupporting
confidence: 78%
“…Additionally, the NOTCH1 downstream effectors, HES1 and HEY1, promote integration of EMT and CSC self-renewal (31,32). Other work has shown that NOTCH1 interacts with NANOG in expanding CSCs (44). Along these lines, we found that the MUC1-CE2F1BAF pathway is necessary for expression of NOTCH1 and NANOG in PC cells.…”
Section: Muc1-c Regulates Lineage Plasticity In the Progression To Nepc By Activating In Part Asupporting
confidence: 78%
“…PEST [17]) may be sufficient to drive tumorigenesis in some instances, the majority of solid tumors with oncogenic Notch signaling might instead harbor aberrations in regulatory proteins (e.g. NUMB [18], TBC1D15 [19]), signaling partners, or relative dosage [20]. Thus, the role of Notch in tumorigenesis may be context dependent, acting most convincingly in cells already poised for transformation.…”
Section: Gamma Secretase Inhibitors and The Notch Pathwaymentioning
confidence: 99%
“…NICD1 signaling was not sufficient to induce cancer initiation but could cooperate with AKT, Myc, and Ras/Raf/MAPK to drive formation of prostate adenocarcinoma in mice and promote more aggressive phenotypes in human prostate cancer cells [16]. Accordingly, although mutations in Notch regulatory sequences or domains (e.g., PEST [17]) may be sufficient to drive tumorigenesis in some instances, the majority of solid tumors with oncogenic Notch signaling might instead harbor aberrations in regulatory proteins (e.g., NUMB [18], TBC1D15 [19]), signaling partners, or relative dosage [20]. Thus, the role of Notch in tumorigenesis may be context dependent, acting most convincingly in cells already poised for transformation.…”
Section: Gamma Secretase Inhibitors and The Notch Pathwaymentioning
confidence: 99%
“…The understanding on the tumorigenesis process has been explained during decades according to the clonal evolution model. This model postulates that all cells within a tumor contribute to the maintenance of the tumor at different levels ( 1 ). In the cell, a number of genetic and epigenetic changes accumulate during time, and, by selection, the most aggressive cancer cells drive tumor progression ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model postulates that all cells within a tumor contribute to the maintenance of the tumor at different levels ( 1 ). In the cell, a number of genetic and epigenetic changes accumulate during time, and, by selection, the most aggressive cancer cells drive tumor progression ( 1 , 2 ). Therefore, any cancer cell can become highly malignant, contributing to metastases and the resistance against therapies ( 2 ).…”
Section: Introductionmentioning
confidence: 99%